Using features of meaningful experiences to guide primary physical education practice. (August 2019) - Beni, Stephanie; Fletcher, Tim; Chróinín, Déirdre Ní
Providing meaningful experiences in physical education has long been identified as a key objective for teachers to strive toward. Supported by a critical friend, a beginning teacher used self-study methodology to analyse ways she drew from the features of meaningful experiences to guide her planning and instruction in primary physical education. Data from a striking/fielding games (e.g. softball, cricket) unit were collected and analysed. Results demonstrate how the teacher came to use the features of meaningful experiences (i.e. social interaction, fun, challenge, motor competence, personally relevant learning, and delight) in integrated ways to guide her planning and instruction in physical education. Through committing to prioritising meaningfulness and reconceptualising ways an experience may be meaningful, the teacher was able to foster these experiences for students primarily through using features of meaningful experiences to filter her decisions. This study offers preliminary support for pedagogies and approaches teachers may use to prioritise meaningful experiences in primary physical education.